95 Differential trends in fall-related fracture and non-fracture hospitalisations for people with dementia. (1st September 2016) - Harvey, Lara; Mitchell, Rebecca; Draper, Brian; Brodaty, Henry; Close, Jacqueline
Abstract : Background: Injury, predominantly fall-related injury, is the most common reason for hospitalisation for people with dementia. Trends in fall-related injury hospitalisations for older people generally have changed over the past decade. It is unknown what impact dementia has on these trends. Methods: Fall-related injury hospitalisations during 1 January 2003 to 31 December 2012 for people aged 65 and older admitted to a hospital in New South Wales, Australia were identified. Hospitalisation records were probabilistically linked to provide comprehensive person-based records. Rates were age-standardised to the 2001 Australian Standard population. Trends over time were analysed using negative binomial regression analysis Results: There were 52, 502 hospitalisations for people with dementia and 203, 330 for people without dementia. People with dementia were more likely to be admitted for a hip fracture (ARR 1.76; 95% CI: 1.73–1.79, p < 0.0001) and traumatic brain injury (TBI) (ARR 1.08; 95% CI: 1.03–1.14, p = 0.0027), but less likely to be admitted for other (non-hip) fractures (ARR 0.72; 95% CI: 0.71–0.73, p < 0.0001) or non-fracture injuries (ARR 0.96; 95% CI: 0.95–0.97, p < 0.001). Hospitalisation rates for people with dementia decreased by 4.2% (95% CI: −5.6−2.7, p < 0.001) per annum for hip fractures and 1.6% (95% CI: 2.3−0.8, p < 0.001) per annum for other fractures, but increased by 7.5% (95% CI: 4.2–10.8%, p < 0.0001) for TBI and 2.0% (95% CI: 0.1–4.0, p = 0.0388) for other non-fracture injuries. In contrast, hip fracture hospitalisation rates remained constant and other fracture and non-fracture injuries increased for people without dementia. Conclusions: Fall-related fracture rates, notably hip fractures, have decreased over the past ten years in people with dementia, whilst there has not been a corresponding decrease in people without dementia. Rates for non-fracture injuries including TBI have increased in both people with and without dementia. The reasons for these differences are not clear.